Evaluation of International Prostate Symptom Score and Quality of Life Following Transurethral Resection of Prostate in Benign Prostatic Hyperplasia (Bangladesh Journal of Urology, 2020)
Objectives: Evaluation of the international prostate symptom score(IPSS) and quality of life score before and following TURP in BPH patients and correlation with objective parameters(Qmax and PVR).Methods: This purposive clinical trial was carried out in the Department of Urology, Sir Salimullah Medical College and Mitford Hospital, Dhaka, from January 2008 to December 2008. Total fifty patients between 50-72 years attending for the treatment of BPH with LUTS were included for the study according to inclusion & exclusion Patients with carcinoma prostate riteria. Selected patients underwent transurethral resection of prostate. All of them had baseline IPSS, QoL score, Qmax, voided volume, voiding time and PVR. They were followed after 1 month and 3 months with same parameter and compared with the baseline values. Correlation of IPSS and QoL score was done with Qmax and PVR.Results: The baseline IPSS in this study was 25.18±1.45. At one month and three months follow up visits after TURP, the IPSS was decreased to 15.0±1.07 and 8.14±0.76 respectively. The mean QoL score was 5.30± 0.46 before TURP. After one month of TURP it was 3.20± 0.45 and after 3 months of TURP it was 1.86 ± 0.57. There was significant negative correlation between the QoL score and Qmax in the preoperative period (r = -0.606, p=0.001), at the 1st follow up visit after one month of TURP (r = -0.171, p=0.235) and at the 2nd follow visit after three months of TURP (r = -0.680, p =0.001). There was positive correlation between the QoL score and PVR in the preoperative period (r = 0.394, p=0.005), at the 1st follow up visit after one month of TURP (r = 0.047, p =0.748) and at the 2nd follow up visit after three months of TURP (r = 0.471, p=0.235).Conclusion: There was significant improvement of quality of after TURP and There was significant negative correlation between the QoL score and Qmax and positive correlation between the QoL score and PVR.Bangladesh Journal of Urology, Vol. 15, No. 2, July 2012 p.27-32